Microglial Pten safeguards postnatal integrity of the cortex and sociability - Zhou, Xing; Wei, Jiacheng; Li, Liang; Shu, Zhenfeng; You, Ling; Liu, Yang; Zhao, Ruozhu; Yao, Jiacheng; Wang, Jianbin; Luo, Minmin; Shu, Yousheng; Yuan, Kexin; et al. (Frontiers in Immunology, 2022)
Microglial abnormalities may contribute to neurodevelopmental disorders. PTEN is implicated as a susceptibility gene for autism spectrum disorders and its germline ablation in mice causes behavioral abnormalities. Here we find postnatal PTEN deletion in microglia causes deficits in sociability and novel object recognition test. Mutant mice harbor markedly more activated microglia that manifest enhanced phagocytosis. Interestingly, two-week postponement of microglia PTEN ablation leads to no social interaction defects, even though mutant microglia remain abnormal in adult animals. Disturbed neurodevelopment caused by early PTEN deletion in microglia is characterized by insufficient VGLUT1 protein in synaptosomes, likely a consequence of enhanced removal by microglia. In correlation, in vitro acute slice recordings demonstrate weakened synaptic inputs to layer 5 pyramidal neurons in the developing cortex. Therefore, microglial PTEN safeguards integrity of neural substrates underlying sociability in a developmentally determined manner.